Предмет: Математика,
автор: Ксюша23112003
Помогите решить уравнение (x-1)(x-1)=(x+3)(x+2)
Ответы
Автор ответа:
0
(x-1)(x-1)=(x+3)(x+2)
x'-x-x-1=x'+2x+3x+6
x'-2x-1-x'-5x-6=0
-7x-7=0
-7x=7
x=-1
x'-x-x-1=x'+2x+3x+6
x'-2x-1-x'-5x-6=0
-7x-7=0
-7x=7
x=-1
Автор ответа:
0
x^2 -1=x^2 +2x+3x+6
x^2 -1=x^2+5x+6
x^2 -1- x^2-5x-6=0
(х в квадрате и минус х в квадрате уходят)
-5x-7=0
-5x=7
x= - 7/5
x= - 1.4
Похожие вопросы
Предмет: Геометрия,
автор: tt05731921
Предмет: Русский язык,
автор: yermakhanzhomart
Предмет: Қазақ тiлi,
автор: alinapopova396
Предмет: Геометрия,
автор: ЪЁДОГО
Предмет: Алгебра,
автор: Kopochka